The Effect of Calcitonin Gene-Related Peptide Monoclonal Antibodies on Quality of Life among Migraine Patients: Pilot Study at the Hospital of Lithuanian University of Health Sciences Kaunas Clinics - Remenčiūtė, Monika; Varžaitytė, Greta; Žemgulytė, Gintarė (Acta medica Lituanica, 2024)
Background: Migraine has a negative impact on patients’ quality of life, with the frequency of attacks being associated with greater disability and poorer health status. Frequent migraine-type headaches require prophylactic treatment, which has so far been of limited effectiveness until advent of calcitonin gene-related peptide (CGRP) monoclonal antibody.Materials and Methods: A prospective analysis was conducted of data from 41 migraine patients who experienced 4 or more monthly migraine days (MMD) longer than three months. At the beginning of the study, treatment with monoclonal antibodies against CGRP (fremanezumab 225 mg or erenumab 70 or 140 g per month) was prescribed according to the indications. The effect of the medications was evaluated after 3-month period.Results: The mean age of patients was 37.17 (±11.78) years. It was found that 17 patients (41.5%) had episodic migraine (EM) and 24 (58.5%) had chronic migraine (CM). Fremanezumab was prescribed to 26 patients (63.4%) and erenumab to 15 patients (36.6%); among the latter, 13 patients used 70 mg/month and 2 patients used 140 mg/month. Three months after treatment, CM changed to EM for 19 patients (79.2%), 27 patients (65.9%) had ≥50% reduction in the number of MMD and total migraine disability assessment (MIDAS) score was reduced by >50% in 31 patients (75.6%). Also, all areas of quality of life of patients were improved after 3 months continued treatment compared to baseline.Conclusions: For more than half the patients using fremanezumab or erenumab after 3-month period, MMD decreased by ≥50% and total MIDAS score by >50 points. All areas of quality of life were improved after prophylactic treatment of migraine.